Preparation method and application of MnS (at) ZIF-67 p-n heterojunction composite material

Synthesis and coating of α-MnS@ZIF-67 p-n heterojunction composite materials by hydrothermal method, solving the problems of limited absorption and recombination of existing photocatalysts when treating organic dyes, significantly improving the photocatalytic degradation efficiency of RhB and stability.

CN119259118APending Publication Date: 2025-01-07HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411410067.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When treating organic dyes, existing photocatalysts have problems such as limited visible light absorption, rapid recombination of photogenerated electron-hole pairs and environmental toxicity, and the differences in photocatalytic properties of semiconductor photocatalysts at different exposed surfaces have not been fully utilized.

Method used

α-MnS with cube and octahedral nanostructures were synthesized by hydrothermal method and coated with ZIF-67 nanoparticles to construct a p-n heterojunction for photocatalytic degradation of RhB, optimize charge carrier separation and Light absorption capacity.

Benefits of technology

The charge carrier separation and light absorption capacity of the photocatalyst is improved, the photocatalytic degradation efficiency of RhB is significantly improved, and the photocatalytic performance and stability are improved through crystal surface engineering and the construction of p-n junctions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259118A_ABST
    Figure CN119259118A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of novel photocatalytic materials, and discloses a preparation method and application of a MnS (at) ZIF-67 p-n heterojunction composite material, and the preparation method comprises the following synthesis steps: S1, synthesizing alpha-MnS powder by a hydrothermal method; s2, the alpha-MnS powder is dispersed in deionized water, and turbid liquid is obtained; and adding cobalt chloride hexahydrate and 2-methylimidazole into the turbid liquid, violently stirring, standing, aging, washing and drying to obtain the MnS (at) ZIF-67 p-n heterojunction composite material. The alpha-MnS (at) ZIF-67 p-n heterojunction composite material prepared by the preparation method disclosed by the invention shows enhanced charge carrier separation and excellent light absorption capability, and is beneficial to efficient photocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new photocatalytic materials, and in particular to a preparation method and application of a MnS@ZIF-67 pn heterojunction composite material. Background Art

[0002] Organic dyes are widely used in various industries such as textiles, papermaking, and plastics, resulting in large amounts of dye-containing wastewater discharged into the environment. The presence of these dyes in water bodies can be harmful to aquatic organisms and human health due to their toxic and carcinogenic properties. Therefore, the removal of organic dyes from wastewater has become an important environmental issue. Among various treatment methods, heterogeneous photocatalysis has emerged as a promising approach for the degradation of organic pollutants. Semiconductor photocatalysts, such as TiO2, ZnO, and PbBiO2X, have been widely studied for the photocatalytic degradation of organic dyes. However, these materials often suffer from limited visible light absorption, rapid recombination of photogenerated electron-hole pairs, and environmental toxicity.

[0003] Among various photocatalyst materials, metal-organic frameworks (MOFs) have attracted great attention due to their unique structural and functional properties. ZIF-67 is a cobalt-based MOF that shows great potential as an n-type photocatalyst due to its high specific surface area, tunable porosity, easy synthesis method, and excellent chemical and thermal stability. Park et al. found that ZIF-67 exhibits strong light-harvesting ability in the NIR to UV region and has excellent photocatalytic performance. Kong et al. found that the cobalt center can help capture CO2 molecules in photocatalytic CO2 reduction. In addition, the presence of the cobalt center in the ZIF-67 structure can promote the separation and transfer of photogenerated charge carriers, thereby improving the photocatalytic performance. Therefore, it is expected that the performance of the photocatalyst can be further improved by composite ZIF-67 with other semiconductor photocatalysts.

[0004] Recently, manganese sulfide (MnS) has attracted great attention as a potential p-type photocatalyst due to its unique optical and electronic properties. MnS exists in two main crystalline phases: stable cubic α-MnS and metastable hexagonal γ-MnS. The α-MnS phase is particularly suitable for photocatalytic applications due to its suitable band gap energy, high charge carrier mobility and good stability. Swathi et al. synthesized α-MnS nanostructures with enhanced electrochemical water oxidation and photocatalytic hydrogen production. Liu et al. prepared α-MnS with Bi2MoO6 for efficient visible light photocatalytic CO2 reduction and stability. Chang et al. coupled α-MnS with Bi4O5Br2, constructed a pn junction, and studied the charge separation behavior.

[0005] In addition, the exposed crystal facets of semiconductor photocatalysts can significantly affect the electronic structure, surface reactivity, and charge carrier dynamics, which are key factors determining the overall photocatalytic efficiency. Different crystal facets may exhibit different adsorption characteristics, active site density, and charge separation / transfer capabilities, resulting in different photocatalytic activities. Previous studies have demonstrated the importance of controlling the exposed crystal facets in various photocatalyst systems such as TiO2 and BiVO4. For example, the (110) crystal facet of Ag3PO4 has been shown to have higher surface energy and better activity than the (100) crystal facet. Similar results have been observed for other semiconductors with different exposed facets. The photocatalytic performance of semiconductor materials can be optimized by selectively exposing specific crystal facets with ideal properties. However, in some literatures, α-MnS cubes with exposed (001) facets and octahedra with exposed (111) facets have been synthesized, and the photocatalytic performance between cubes and octahedra with different exposed facets is rarely studied. Summary of the invention

[0006] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a method for preparing a MnS@ZIF-67 pn heterojunction composite material and its application, wherein α-MnS with cubic nanostructures and octahedral nanostructures is synthesized by a simple hydrothermal method, and these α-MnS nanostructures are further coated with ZIF-67 nanoparticles to construct a pn heterojunction, which is used for RhB photocatalytic degradation. The α-MnS@ZIF-67 pn heterojunction composite material prepared by the present invention shows enhanced charge carrier separation and excellent light absorption capacity, which is conducive to efficient photocatalysis.

[0007] Technical solution: On the one hand, the present invention provides a method for preparing a MnS@ZIF-67 pn heterojunction composite material, comprising the following steps: S1, hydrothermal method to synthesize α-MnS powder; S2. Dispersing the α-MnS powder in deionized water to obtain a suspension; then adding cobalt chloride hexahydrate and 2-methylimidazole to the suspension, stirring vigorously, standing for aging, washing, and drying to obtain a MnS@ZIF-67 pn heterojunction composite material.

[0008] Further, in S1, the specific synthesis method of the α-MnS powder is: disperse polyvinyl pyrrolidone in deionized water, then add N,N-dimethylformamide, and then slowly add manganese acetate and sodium sulfide, mix evenly, hydroheat at 180-200°C for 20-24h, cool, wash, and dry to obtain α-MnS cubes; Or, in S1, the specific synthesis method of the α-MnS powder is: disperse polyvinyl pyrrolidone in deionized water, slowly add manganese acetate and sodium sulfide, mix evenly, hydroheat at 180-200° C. for 20-24 hours, cool, wash, and dry to obtain α-MnS octahedron.

[0009] Furthermore, in S2, the added amount of the cobalt chloride hexahydrate is 0.12-0.35 mmol.

[0010] Furthermore, in S2, the added amount of the 2-methylimidazole is 0.46-1.38 mmol.

[0011] Furthermore, in S2, the mass of the α-MnS powder is 180-220 mg.

[0012] Furthermore, in S2, the vigorous stirring time is 1.5-2.5h.

[0013] Preferably, in S2, the static aging time is 22-26 hours.

[0014] Preferably, in S2, the specific operation of washing is: washing with deionized water 6-8 times.

[0015] Furthermore, in S2, the specific conditions of the drying are: the drying temperature is 50-70 °C, and the drying time is 10-14h.

[0016] On the other hand, the present invention provides an application of a MnS@ZIF-67 pn heterojunction composite material prepared by any of the methods described above in the photocatalytic degradation of RhB.

[0017] Synthesis principle: The synthesis process of the α-MnS@ZIF-67 pn heterojunction composite material prepared by the present invention is as follows Figure 1 a. First, the α-MnS structure was synthesized by direct hydrothermal method. Dimethylformamide (DMF), as a surfactant, plays a key role in controlling the surface morphology of α-MnS. In the present invention, α-MnS with cubic nanostructure and octahedral nanostructure was synthesized by simple hydrothermal reaction: Figure 1 b, adding DMF during the hydrothermal process can construct a microcubic α-MnS with six exposed {001} faces. In contrast, omitting DMF during the hydrothermal process can produce an octahedral α-MnS ( Figure 1 f), which has eight exposed {111} facets. Subsequently, Co was briefly stirred in deionized water. 2+ions and 2-methylimidazole, integrating these α-MnS cubes or octahedra with ZIF-67, and further coating these α-MnS cubes or octahedra with ZIF-67 nanoparticles to construct pn heterojunctions to form cubic α-MnS@ZIF-67 pn heterojunction composites or octahedral α-MnS@ZIF-67 pn heterojunction composites.

[0018] Beneficial effects: The present invention prepares a cubic α-MnS@ZIF-67 pn heterojunction composite material or an octahedral α-MnS@ZIF-67 pn heterojunction composite material, and uses it for RhB photocatalytic degradation. In the α-MnS@ZIF-67 pn heterojunction composite material prepared by the present invention, the combination of α-MnS and ZIF-67 constructs a pn junction with a built-in electric field, extends the response to the visible light region, and promotes the mobility of charge carriers, thereby improving the overall photocatalytic performance, so that the composite material shows enhanced charge carrier separation and excellent light absorption ability, which is more conducive to efficient photocatalysis. In addition, the cubic α-MnS@ZIF-67 pn heterojunction composite material or octahedral α-MnS@ZIF-67 pn heterojunction composite material constructed by the present invention demonstrates the influence of exposure surface, band structure and Karys behavior on the photocatalytic degradation efficiency. The present invention provides new insights into the development of high-performance and stable metal-organic framework (MOF)-based photocatalysts through crystal face engineering and pn junction construction. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 The synthesis process diagram of the α-MnS@ZIF-67 pn heterojunction composite material prepared by the present invention and its SEM diagram and element mapping diagram; Figure 2 XRD diagram, magnified diffraction peak diagram, and TEM diagram of the α-MnS@ZIF-67 pn heterojunction composite material prepared by the present invention and the comparative example; Figure 3 The XPS spectra of the α-MnS@ZIF-67 pn heterojunction composite material prepared by the present invention and the comparative example; Figure 4 UV-vis diffuse reflectance spectrum, Tauc diagram, Mott-schottky diagram, and XPS valence band spectrum of the α-MnS@ZIF-67 pn heterojunction composite material prepared by the present invention and the comparative example; Figure 5 Transient photocurrent response measurement graph, EIS graph, and PL graph of the α-MnS@ZIF-67 pn heterojunction composite material prepared by the present invention and the comparative example; Figure 6The photocatalytic degradation diagram of RhB of the α-MnS@ZIF-67 pn heterojunction composite material prepared by the present invention and the comparative example; Figure 7 Schematic diagram of photocatalysis of the α-MnS@ZIF-67 pn heterojunction composite material prepared in the present invention. DETAILED DESCRIPTION

[0020] The present invention is described in detail below in conjunction with the embodiments.

[0021] Implementation 1: This embodiment provides a method for preparing a MnS@ZIF-67 pn heterojunction composite material, which is specifically as follows: (1) Synthesis of α-MnS cubes: 3 g of polyvinylpyrrolidone (PVP) was completely dispersed in 30 ml of deionized water by vigorous stirring for 30 min. Subsequently, the mixture was enriched by adding 1 ml of N,N-dimethylformamide (DMF), and then 2 mmol of manganese acetate and 4.5 mmol of sodium sulfide were slowly introduced. The mixture was then stirred for another 30 min to ensure complete homogeneity. The resulting solution was carefully transferred to a 50 ml autoclave, which was then sealed and placed in a forced air drying oven and heated at 190 °C for 20 h. After the heating cycle was completed, the autoclave was naturally cooled to room temperature to promote the gradual stabilization of the reaction product. The resulting green precipitate was carefully purified using ethanol and deionized water through repeated washing cycles. The process was repeated six times to ensure the removal of any residual impurities and dried in an oven at 60 °C to obtain α-MnS cubic powder.

[0022] Synthesis of α-MnS@ZIF-67 pn heterojunction composite: 200 mg of the α-MnS cubic powder synthesized above was dispersed in 40 mL of deionized water. Subsequently, 0.12 mmol of cobalt chloride hexahydrate (CoCl2·6H2O) and 0.46 mmol of 2-methylimidazole were added to the suspension and the stirring process was started, which lasted for 2 h. After this, the mixture underwent an aging process for 24 h, thus completing the reaction stage. After the reaction, the precipitated product was carefully washed with deionized water on six different occasions to remove any remaining impurities. The washed material was then dried in an oven at 60 °C for 12 h to achieve anhydrous state. The cubic α-MnS@ZIF-67 pn heterojunction composite was obtained, denoted as cMZ5.

[0023] Implementation 2: This embodiment is substantially the same as Embodiment 1, except that in this embodiment, the amount of cobalt chloride hexahydrate (CoCl2·6H2O) added is 0.23 mmol, and the amount of 2-methylimidazole added is 0.92 mmol. The cubic α-MnS@ZIF-67 pn heterojunction composite material prepared in this embodiment is denoted as cMZ10.

[0024] Apart from this, this embodiment is completely the same as Embodiment 1 and will not be described in detail here.

[0025] Implementation 3: This embodiment is substantially the same as Embodiment 1, except that in this embodiment, the amount of cobalt chloride hexahydrate (CoCl2·6H2O) added is 0.35 mmol, and the amount of 2-methylimidazole added is 1.38 mmol. The cubic α-MnS@ZIF-67 pn heterojunction composite material prepared in this embodiment is denoted as cMZ15.

[0026] Apart from this, this embodiment is completely the same as Embodiment 1 and will not be described in detail here.

[0027] Implementation 4: Synthesis of α-MnS octahedron: 3 g of polyvinyl pyrrolidone (PVP) was completely dispersed in 30 ml of deionized water by vigorous stirring for 30 min. Subsequently, 2 mmol of manganese acetate and 4.5 mmol of sodium sulfide were slowly introduced. Then, the mixture was stirred for another 30 min to ensure complete homogeneity. The resulting solution was carefully transferred to a 50 ml autoclave, which was then sealed and placed in a forced air drying oven and heated at 190 °C for 20 h. After the heating cycle was completed, the autoclave was naturally cooled to room temperature to promote the gradual stabilization of the reaction product. The resulting green precipitate was carefully purified using ethanol and deionized water through repeated washing cycles. The process was repeated six times to ensure the removal of any residual impurities and dried in an oven at 60 °C to obtain α-MnS octahedron powder.

[0028] Synthesis of α-MnS@ZIF-67 pn heterojunction composite material: 200 mg of the α-MnS octahedral powder synthesized above was dispersed in 40 mL of deionized water. Subsequently, 0.12 mmol of cobalt chloride hexahydrate (CoCl2·6H2O) and 0.46 mmol of 2-methylimidazole were added to the suspension and the stirring process was started, which lasted for 2 h. After this, the mixture underwent an aging process for 24 h, thus completing the reaction stage. After the reaction, the precipitated product was carefully washed with deionized water on six different occasions to remove any remaining impurities. The washed material was then dried in an oven at 60 °C for 12 h to achieve anhydrous state. The octahedral α-MnS@ZIF-67 pn heterojunction composite material was obtained, denoted as oMZ5.

[0029] Implementation 5: This embodiment is substantially the same as Embodiment 4, except that in this embodiment, the amount of cobalt chloride hexahydrate (CoCl2·6H2O) added is 0.23 mmol, and the amount of 2-methylimidazole added is 0.92 mmol. The octahedral α-MnS@ZIF-67 pn heterojunction composite material prepared in this embodiment is denoted as oMZ10.

[0030] Apart from this, this embodiment is exactly the same as embodiment 4 and will not be described in detail here.

[0031] Implementation 6: This embodiment is substantially the same as Embodiment 4, except that in this embodiment, the amount of cobalt chloride hexahydrate (CoCl2·6H2O) added is 0.35 mmol, and the amount of 2-methylimidazole added is 1.38 mmol. The octahedral α-MnS@ZIF-67 pn heterojunction composite material prepared in this embodiment is recorded as oMZ15.

[0032] Apart from this, this embodiment is exactly the same as embodiment 4 and will not be described in detail here.

[0033] Comparative Example 1: 3 g of polyvinylpyrrolidone (PVP) was completely dispersed in 30 ml of deionized water by vigorous stirring for 30 min. Subsequently, the mixture was enriched by adding 1 ml of N,N-dimethylformamide (DMF), and then 2 mmol of manganese acetate and 4.5 mmol of sodium sulfide were slowly introduced. Then, the mixture was stirred for another 30 min to ensure complete homogeneity. The resulting solution was carefully transferred to a 50 ml autoclave, which was then sealed and placed in a forced air drying oven and heated at 190 °C for 20 h. After the heating cycle was completed, the autoclave was naturally cooled to room temperature to promote the gradual stabilization of the reaction product. The resulting green precipitate was carefully purified using ethanol and deionized water through repeated washing cycles, and the process was repeated six times to ensure the removal of any residual impurities and dried in an oven at 60 °C to obtain α-MnS cubic powder.

[0034] Comparative Example 2: 3 g of polyvinyl pyrrolidone (PVP) was completely dispersed in 30 ml of deionized water by vigorous stirring for 30 min. Subsequently, 2 mmol of manganese acetate and 4.5 mmol of sodium sulfide were slowly introduced. The mixture was then stirred for another 30 min to ensure complete homogeneity. The resulting solution was carefully transferred to a 50 ml autoclave, which was then sealed and placed in a forced air drying oven and heated at 190 °C for 20 h. After the heating cycle was completed, the autoclave was naturally cooled to room temperature to promote the gradual stabilization of the reaction product. The resulting green precipitate was carefully purified using ethanol and deionized water through repeated washing cycles, and the process was repeated six times to ensure the removal of any residual impurities and dried in an oven at 60 °C to obtain α-MnS octahedral powder.

[0035] Comparative Example 3: ZIF-67: 0.238 g of cobalt chloride hexahydrate (CoCl2·6H2O) and 1.642 g of 2-methylimidazole were dissolved in 20 ml of deionized water. The solution was then subjected to vigorous stirring for two hours to ensure thorough mixing and homogeneity. After the stirring stage, the reaction mixture was left to stand for 24 h to allow for an aging process to facilitate the completion of crystal growth. Subsequently, the resulting dark purple precipitate was carefully washed with deionized water for six consecutive cycles. After the washing process was completed, it was transferred to a 60 °C oven and dried for 12 hours to obtain ZIF-67.

[0036] The photodegradation performance of the photocatalyst prepared above was analyzed and used for the photocatalytic degradation of rhodamine B (RhB). The specific method is as follows: The photodegradation of rhodamine B (RhB) was evaluated in a 150 mL glass reactor, where 10 mg of the synthesized photocatalyst was dispersed in 100 mL of a 10 mg / L RhB aqueous solution. Illumination was provided by a fluorescent lamp (CEAU lamp), irradiated vertically and maintained at a distance of 15 cm from the light source. To selectively exclude UV radiation, a 420 nm cutoff filter was used to ensure that only visible light reached the reaction mixture. Oxygen was continuously bubbled through the RhB solution at a flow rate of 5 mL / min throughout the experiment, while magnetic stirring was performed to maintain a uniform temperature of 25 ± 2 °C. Before starting the irradiation, the suspension was stirred in the dark at room temperature for 30 min to establish the adsorption-desorption equilibrium. Quantification of the residual RhB concentration was achieved using a UV-visible spectrophotometer (UV-3600PC, Shimadzu), enabling precise monitoring of the photodegradation efficiency over time.

[0037] Synthesis, characterization and photocatalytic performance analysis: The synthesis process of the α-MnS@ZIF-67 pn heterojunction composite material prepared by the present invention is as follows: Figure 1 a. First, the α-MnS structure was synthesized by direct hydrothermal method. Figure 1 b. After adding DMF during the hydrothermal process, microcubic morphology of α-MnS with six exposed {001} facets was observed. The diameter of these microconduits was about 1.2 μm. In contrast, omitting DMF during the hydrothermal process resulted in octahedral morphology of α-MnS with eight exposed {111} facets, forming octahedrons with diameters ranging from 0.8 μm to 2.5 μm. Subsequently, Co was briefly stirred in deionized water. 2+ ions and 2-methylimidazole to integrate these α-MnS cubes or octahedra with ZIF-67. Figure 1 It can be clearly seen in Figure c and g that many small ZIF-67 nanoparticles are deposited on the surface of the α-MnS core, with an average size of tens of nanometers. Figure 1 d and h show SEM images of pure ZIF-67, in which the nanoparticles aggregated to form microspheres. Figure 1 e and i show the corresponding elemental mapping images of Mn, S, Co, N, and C from α-MnS and ZIF-67. Mn and S elements maintain their cubic and octahedral shapes, respectively, while Co, N, and C elements are randomly distributed on the surface, indicating the coexistence of α-MnS and ZIF-67. The coexistence of α-MnS and ZIF-67 was further confirmed by XRD and TEM analysis.

[0038] The crystal structures of the α-MnS samples synthesized in the present invention are divided into two different series, which have been elucidated by X-ray diffraction (XRD) analysis, such as Figure 2ac. The XRD pattern shows significant and clear peaks of cubic and octahedral α-MnS structures, located at angles of approximately 29.6°, 34.7°, 49.3°, and 61.4°. According to JCPDS (16-0518), these peaks correspond to the (111), (200), (220), and (222) crystal planes of α-MnS. The diffraction signal of ZIF-67 is significantly weakened compared to the α-MnS-based sample, which may be attributed to its relatively low crystallinity. The enlarged diffraction peaks of ZIF-67 are shown in Figure 3 c, where the original ZIF-67 shows its characteristic peaks at angles of approximately 7.5°, 10.4°, 12.7°, 16.5°, and 18.1°. They are related to the (110), (002), (112), (013), and (222) crystal planes of ZIF-67, respectively. When α-MnS and ZIF-67 were co-melted to prepare cMZx and oMZx composites, the main phase was α-MnS. At the same time, a small amount of MnOx was found in the cMZx and oMZx samples, which was the result of the aging process, which lasted for 24 hours. The XRD characteristics of ZIF-67 were not obvious, which was the result of its reduced crystallinity.

[0039] Transmission electron microscopy (TEM) and high-resolution TEM (HR-TEM) images of cMZ10 and oMZ10 samples further confirmed the simultaneous existence of ZIF-67 and α-MnS, as shown in Figure 2. Figure 2 As shown in dg. Figure 2 The images in d and f show that the surfaces of α-MnS cubes and octahedra are densely populated with a large number of tiny nanoparticles, confirming the findings of scanning electron microscopy (SEM). In addition, in addition to the lattice fringes corresponding to the α-MnS (200) planes with a spacing of 0.261 nm, larger lattice fringes with a spacing of 0.483 nm were also found, which were attributed to the (222) lattice planes of ZIF-67. TEM images confirm that ZIF-67 nanoparticles are effectively coated on the surfaces of α-MnS cubes and octahedra, forming a heterogeneous structure at the micro / nano scale.

[0040] The elemental composition and chemical state of the prepared α-MnS@ZIF-67 pn heterojunction composites (cMZ10 and oMZ10) were analyzed by X-ray photoelectron spectroscopy (XPS). Figure 3 The survey spectrum of cMZ10, shown in a, reveals the presence of Mn and S elements, which are derived from α-MnS, as well as Co, C, and N elements, indicating ZIF-67. Figure 3 In the Mn 2p spectrum in (b), the double peaks centered at 641.7 eV and 653.3 eV can be attributed to the Mn² in the α-MnS matrix. + ions. Similarly, S² in α-MnS -ions are represented by double peaks at 163.0 eV and 164.1 eV. Co² in ZIF-67 is observed at 780.9 eV and 796.3 eV - The unique peaks of ions further confirm the composite nature of the material. For the C 1s spectrum, Figure 3 e, the binding energies of the cMZ10 sample are 284.8 eV, 286.4 eV, and 288.5 eV, corresponding to C-C, C=N, and C=O chemical bonds, respectively. The existence of the C=N bond is confirmed in the N 1s spectrum at 399.8 eV, as shown in Figure 3 f, the bonding between ZIF-67 and cMZ10 composites is strengthened. Consistent results are also observed in the XPS spectrum of oMZ10 samples, such as Figure 3 These XPS analyses strongly confirm the coexistence of α-MnS and ZIF-67 in the cMZ10 and oMZ10 composites, thus confirming the successful synthesis of the heterostructures.

[0041] In order to evaluate the optical properties and light collection ability of the α-MnS-based photocatalyst synthesized in the present invention, UV-vis diffuse reflectance spectroscopy was used, such as Figure 4 a and 4b. The ZIF-67 component exhibits a unique absorption in the range of 500-600 nm, which is attributed to Co² + ions. Meanwhile, α-MnS cubes and octahedra exhibit broad absorption in the UV-visible spectrum. When ZIF-67 was introduced into cMZX and oMZX composites, the light absorption capacity was significantly enhanced compared with that of pristine α-MnS. The absorption intensity gradually increased with the increase of ZIF-67 content. This indicates that there is a synergistic effect between the components, which has the potential to improve the photocatalytic activity under visible light.

[0042] To determine the electronic band structure, the band gaps (Eg) of α-MnS cube, α-MnS octahedron, and ZIF-67 were estimated using the Tauc plot, as shown in Figure 4 c. Using the empirical Tauc relation, αhν=A(hν−Eg) 1 / 2 , where α represents the absorption coefficient and A is a constant, we calculated the band gaps of α-MnS cube, α-MnS octahedron, and ZIF-67 to be 2.24 eV, 2.14 eV, and 1.97 eV, respectively. It is noteworthy that α-MnS cube has a slightly wider band gap than α-MnS octahedron. This difference may be caused by differences in exposed crystal facets and particle size, which affect the electronic structure and optical properties of the materials. These insights into the optical and electronic properties provide a basis for the behavior of the materials under light, paving the way for their application in photocatalytic processes.

[0043] In order to further understand the band structure of α-MnS@ZIF-67 pn heterojunction composites, Figure 4 dh gives the Mott-schottky plots of ZIF-67, α-MnS cube, cMZ10, α-MnS octahedron, and oMZ10. Figure 4 As shown in d, the ZIF-67 sample shows C -2 The positive slope of the graph indicates that ZIF-67 is an n-type semiconductor. C -2 The curves all show a negative slope, indicating that α-MnS is a p-type semiconductor. The V-shaped curves of cMZ10 and oMZ10 composites are inverted V-shaped, indicating that n-type ZIF-67 and p-type α-MnS form a pn junction after combination. Figure 4 As shown in Fig. 5, the flat band potentials of ZIF-67 and α-MnS are -0.90 V and -0.05 V, respectively, compared to Ag / AgCl. It is known that the valence band of a p-type semiconductor is more positive than its flat band potential, about 0.1 V or 0.2 V. Selecting 0.2 V, the valence band top of α-MnS is +0.15 V, which is +0.15 V compared to Ag / AgCl. According to the formula E(NHE) = E(Ag / AgCl) + 0.197, the valence band top potential (EVB) of the α-MnS cube is converted to +0.35 V, vs NHE. The conductor band bottom (ECB) of the α-MnS cube is calculated to be -1.89 V, vs NHE. The conduction band of an n-type semiconductor is 0.2 V more negative than the flat band potential. Therefore, the ECB and EVB of ZIF-67 were calculated to be −0.90 V and +1.07 V, vs. NHE in the cMZ10 composite. Similarly, the ECB and EVB of ZIF-67 and α-MnS octahedron in oMZ10 were (−0.87 V and +1.10 V, vs. NHE) and (−1.79 V and +0.35 V, vs. NHE), respectively.

[0044] In addition, Figure 4 It is noted in Fig. 1 that the XPS valence band top is estimated to be +0.75 eV, which reveals the energy gap between the valence band top of α-MnS and the Fermi level of the XPS instrument (Al, 4.1 eV, vs vacuum level). Therefore, the valence band top of the cMZ10 and oMZ10 composites is calculated to be +0.45 eV, vs NHE. This is consistent with the above Mott-Schottky analysis.

[0045] In order to gain a deeper understanding of the electronic structure of the α-MnS@ZIF-67 pn heterojunction composite, Mott–Schottky analysis was performed. The composite diagrams of ZIF-67, α-MnS cube, cMZ10, α-MnS octahedron, and oMZ10 are shown in Figure 2. Figure 4As shown in dh. Figure 4 As shown in d, ZIF-67 is in C -2 The voltage graph shows a positive slope, indicating its n-type semiconductor characteristics. In contrast, the α-MnS cube ( Figure 4 e) and octahedron ( Figure 4 g) both show a negative slope, confirming their p-type semiconductor properties. It is observed that the cMZ10 and oMZ10 composites have obvious inverted V-shaped curves ( Figure 4 f and 4h), indicating that a pn junction is formed on the composition of p-type α-MnS and n-type ZIF-67. The flat band potential was determined from the intercepts of each Mott-Schottky plot, yielding a value of -0.90 V for ZIF-67 and -0.05 V for α-MnS relative to the Ag / AgCl reference electrode. Considering that the valence band edge of a p-type semiconductor is usually +0.2 V above its flat band potential, the valence band maximum (VBM) of α-MnS was calculated to be +0.15 V vs Ag / AgCl. Using the conversion factor E(NHE) = E(Ag / AgCl) + 0.197, the VBM potential of α-MnS was converted to +0.35 V (vs NHE). Therefore, the conduction band minimum (CBM) of the α-MnS cube was determined to be -1.89 V vs NHE. Considering that the CBM of n-type semiconductors is approximately 0.2 V negative than the flat band potential, the CBM and VBM of ZIF-67 are calculated to be −0.90 V and +1.07 V vs NHE for the cMZ10 composite, respectively. Similarly, for the oMZ10 composite, the CBM and VBM values ​​of ZIF-67 and α-MnS octahedron are (−0.87 V and +1.10 V, vs NHE) and (−1.79 V and +0.35 V, vs NHE), respectively.

[0046] In addition, the XPS valence band spectrum ( Figure 4 i) shows that the VBM is located at approximately +0.75 eV, revealing an energy gap between the VBM of α-MnS and the Fermi level of the XPS instrument (Al Kα, 4.1 eV relative to the vacuum level). Therefore, the VBM of the cMZ10 and oMZ10 composites is calculated to be +0.45 eV vs NHE. This finding is in good agreement with the above Mott-Schottky analysis, providing solid evidence for the electronic structure of the composites.

[0047] To elucidate the dynamics of photoinduced charge carrier separation and migration, transient photocurrent response measurements were performed, e.g. Figure 5a and 5e. The results show that the photocurrent response of cMZ10 and oMZ10 composites is significantly enhanced compared with the original α-MnS and ZIF-67 samples. It is worth noting that the cMZ10 sample shows a better photocurrent intensity than oMZ10, which indicates that it has more efficient photocatalytic performance.

[0048] Figure 5 b and 5f show the Nyquist plots of α-MnS cube cMZ10 and α-MnS octahedron oMZ10 derived from electrochemical impedance spectroscopy (EIS). The reduced semicircle diameters of cMZ10 and oMZ10 indicate a reduced charge transfer resistance, indicating an improved electron mobility in the α-MnS@ZIF-67 pn heterojunction composite.

[0049] To further investigate the recombination and separation characteristics of charge carriers, the photoluminescence (PL) spectra were analyzed, e.g. Figure 5 c and 5g. Lower photoluminescence intensity usually means a decrease in the charge carrier recombination rate and an increase in the photocatalytic activity. In fact, the PL intensity of cMZ10 and oMZ10 composites is significantly reduced relative to that of α-MnS cubic and octahedral, which strongly suggests that the addition of ZIF-67 promotes effective carrier separation in the composites.

[0050] To gain insight into the kinetics of charge carrier transfer in the photocatalyst, the time-resolved PL decay curves of α-MnS cube, cMZ10, α-MnS octahedron, and oMZ10 were obtained, as shown in Fig. Figure 5 d and 5h. The shortened lifetime of charge carriers in the composites relative to pure α-MnS cubes and octahedra implies rapid and efficient charge separation and transfer from α-MnS to ZIF-67. This accelerated kinetics supports an efficient charge relay mechanism at the heterojunction interface, contributing to the enhanced photocatalytic performance of the α-MnS@ZIF-67 pn heterojunction composites.

[0051] To evaluate the photocatalytic efficiency of the synthesized materials, rhodamine B (RhB) was selected as a model pollutant for degradation studies. RhB is a stable dye that hardly decomposes under natural conditions, which was confirmed in control experiments without catalysts. Figure 6As shown in Figure ​a, approximately 20% of RhB was adsorbed onto the surface of pure α-MnS cubes. However, only 4% of RhB was photodegraded under 2 h of illumination. In contrast, pure ZIF-67 showed excellent photocatalytic activity, achieving approximately 50% RhB degradation. After the formation of the α-MnS@ZIF-67 pn heterojunction composite, a significant improvement in the photocatalytic performance was observed, which was particularly evident in the cMZ5, cMZ10, and cMZ15 samples, among which cMZ10 showed the highest activity. Approximately 60% of RhB was adsorbed onto cMZ10, and nearly 90% of the dye was degraded after two hours of irradiation. As we expected, the photocatalytic activities of oMZ5 and oMZ10 exceeded those of pure α-MnS octahedra and ZIF-67. Specifically, oMZ10 showed excellent performance, with approximately 55% of RhB adsorbed and 70% degraded after 120 min of illumination, as shown in Figure ​a. Figure 6 b. These findings highlight the effectiveness of combining α-MnS cubes or octahedra with ZIF-67 nanoparticles to enhance the photocatalytic capabilities of both components. The durability and reusability of photocatalysts are crucial for practical applications. To this end, the cMZ10 sample was subjected to four consecutive cycles of RhB degradation, as shown in Figure 6 c. Even after four rounds of testing, the photocatalyst maintained its high activity, retaining about 90% degradation efficiency, which highlights the excellent stability of the composite material. This robustness is critical for the successful implementation of photocatalysis in environmental remediation and other practical scenarios.

[0052] Reactive oxygen species, namely superoxide radicals (O 2- ), holes (h + The key roles of ) and hydroxyl radicals (·OH) in the photocatalytic degradation mechanism are widely recognized. To clarify the contribution of each species to the observed photocatalytic activity, 0.1 mM O2 - 、h + A specific scavenger of ·OH was introduced into the reaction system. Figure 6 d shows the effect of these scavengers on the photocatalytic efficiency. It is worth noting that the addition of benzoquinone (BQ), a superoxide radical (O2 - ) selective scavenger, resulting in a significant decrease in photocatalytic performance. + )) and 2-propanol (2-PrOH), a scavenger of hydroxyl radicals (·OH), resulted in only a slight decrease in the photocatalytic activity. These findings highlight the role of superoxide radicals (O2 - ) as the main active species in the studied photocatalytic degradation process.

[0053] In order to clarify the enhanced photocatalytic mechanism of α-MnS@ZIF-67 pn heterojunction composites, the photocatalytic schematic diagram of α-MnS@ZIF-67p-n heterojunction composites is shown in Figure 7 As shown in Figure 2. The photocatalytic performance of pure ZIF-67, α-MnS cubes and octahedra is limited in RhB degradation due to low photoelectric conversion efficiency and rapid carrier recombination. After α-MnS is combined with ZIF-67, interfacial charge transfer occurs within the pn heterojunction. In this pn heterojunction, holes in p-type α-MnS migrate toward n-type ZIF-67, while leaving negative charges in α-MnS. At the same time, electrons from n-type ZIF-67 move to p-type α-MnS, depositing positive charges in ZIF-67. This charge separation establishes an internal electric field from n-type ZIF-67 to p-type α-MnS. Under light illumination, charge carriers in both components of the composite are excited. Thanks to the existence of the internal electric field, holes in the valence band (VB) of ZIF-67 are forced to relocate to the VB of α-MnS, while electrons in the conduction band (CB) of α-MnS are driven toward the CB of ZIF-67. Therefore, the pn heterojunction significantly enhances the separation and transfer of electron-hole pairs. The separated electrons can reduce dissolved oxygen (O2) to superoxide radicals (O2 - ), followed by the proton (H + ) react with holes to generate hydroxyl radicals (·OH). These reactive oxygen species, including superoxide radicals, hydroxyl radicals, and holes, effectively oxidize RhB molecules into the final decomposition products, carbon dioxide (CO2) and water (H2O).

[0054] It is noteworthy that the cMZX samples exhibited superior photocatalytic performance compared to the oMZX samples. This performance difference was largely attributed to the difference in exposed facets. The photocatalytic results and photocurrent responses indicated that the charge carrier transfer between the {001} facets of α-MnS and ZIF-67 was more efficient than that between the {111} facets of α-MnS and ZIF-67. This may be a key factor in the enhanced photocatalytic activity. In addition, the relatively small size of cubic α-MnS may help to increase the density of the ZIF-67 nanoparticle composites, enhance the formation of pn heterojunctions, and provide more reaction sites for RhB degradation.

[0055] In summary, the present invention synthesized two series of composite materials, cubic α-MnS@ZIF-67 pn heterojunction and octahedral α-MnS@ZIF-67 pn heterojunction, and characterized and investigated their photocatalytic activity. The effects of exposure surface, band structure and Carex behavior on photocatalytic degradation efficiency were systematically studied. The possible mechanism of photocatalytic degradation of RhB on α-MnS@ZIF-67 pn heterojunction composite materials was also discussed. The composite materials prepared by the present invention showed enhanced charge carrier separation and excellent light absorption capacity, which is more conducive to efficient photocatalysis. At the same time, based on the difference in exposure surface and the relatively small size of cubic α-MnS, it may help to increase the density of ZIF-67 nanoparticle composite materials, enhance the formation of pn heterojunction, and provide more reaction sites for RhB degradation. The photocatalytic performance of the cubic α-MnS@ZIF-67 pn heterojunction composite materials synthesized by the present invention is better.

[0056] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a MnS@ZIF-67 pn heterojunction composite material, characterized in that: The following steps are involved: S1, hydrothermal method to synthesize α-MnS powder; S2. Dispersing the α-MnS powder in deionized water to obtain a suspension; then adding cobalt chloride hexahydrate and 2-methylimidazole to the suspension, stirring vigorously, standing for aging, washing, and drying to obtain a MnS@ZIF-67 pn heterojunction composite material.

2. The method for preparing the MnS@ZIF-67 pn heterojunction composite material according to claim 1, characterized in that: In S1, the specific synthesis method of the α-MnS powder is: disperse polyvinyl pyrrolidone in deionized water, then add N,N-dimethylformamide, and then slowly add manganese acetate and sodium sulfide, mix evenly, hydroheat at 180-200°C for 20-24h, cool, wash, and dry to obtain α-MnS cubes; Or, in S1, the specific synthesis method of the α-MnS powder is: disperse polyvinyl pyrrolidone in deionized water, slowly add manganese acetate and sodium sulfide, mix evenly, hydroheat at 180-200° C. for 20-24 hours, cool, wash, and dry to obtain α-MnS octahedron.

3. The method for preparing the MnS@ZIF-67 pn heterojunction composite material according to claim 1, characterized in that: In S2, the added amount of the cobalt chloride hexahydrate is 0.12-0.35 mmol.

4. The method for preparing the MnS@ZIF-67 pn heterojunction composite material according to claim 1, characterized in that: In S2, the added amount of 2-methylimidazole is 0.46-1.38 mmol.

5. The method for preparing the MnS@ZIF-67 pn heterojunction composite material according to claim 1, characterized in that: In S2, the mass of the α-MnS powder is 180-220 mg.

6. The method for preparing the MnS@ZIF-67 pn heterojunction composite material according to claim 1, characterized in that: In S2, the vigorous stirring time is 1.5-2.5h.

7. The method for preparing the MnS@ZIF-67 pn heterojunction composite material according to claim 1, characterized in that: In S2, the static aging time is 22-26 hours.

8. The method for preparing the MnS@ZIF-67 pn heterojunction composite material according to claim 1, characterized in that: In S2, the specific operation of washing is: washing with deionized water 6-8 times.

9. The method for preparing the MnS@ZIF-67 pn heterojunction composite material according to claim 1, characterized in that: In S2, the specific conditions of the drying are: drying temperature is 50-70 ° C, and drying time is 10-14 h.

10. Use of the MnS@ZIF-67 pn heterojunction composite material prepared by the method according to any one of claims 1 to 9 in the photocatalytic degradation of RhB.